Preparation method and application of novel cross-linked polyarylpyridine anion exchange membrane

By using the polycondensation main chain and quaternary ammonium alkenyl compounds of aryl compounds and 4-acetylpyridine as crosslinking agents in the anion exchange membrane, a crosslinking side chain with excellent microscopic phase separation characteristics is solved. There are problems such as insufficient mechanical properties and low crosslinking in flow batteries, which achieve high ion flux, low swelling and excellent mechanical properties.

CN119463078APending Publication Date: 2025-02-18SUQIAN TIMES ENERGY STORAGE TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411601224.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing anion exchange membranes have problems such as insufficient mechanical properties, low crosslinking, high swelling, high resistance and poor oxidation resistance in liquid flow batteries, which affect the energy efficiency and service life of the battery.

Method used

The main chain is formed by aryl compounds and 4-acetylpyridine polycondensation, and quaternary ammonium salt-type alkenyl compounds are introduced as crosslinking agents. The crosslinking is completed by heating to form a crosslinking side chain with excellent microscopic phase separation characteristics, which enhances the Redox resistance and mechanical properties of the overall film.

Benefits of technology

It realizes high ion flux, low swelling, low film resistance, excellent mechanical properties and oxidation resistance of anion exchange membrane, and is suitable for liquid flow batteries and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463078A_ABST
    Figure CN119463078A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method and application of a novel cross-linked polyarylpyridine anion exchange membrane, and the preparation method comprises the following steps: using one or more aromatic compounds as a polymer monomer main chain, and condensing with 4-acetylpyridine under the catalytic action of superacid to obtain a polymer intermediate; a quaternary ammonium salt alkenyl compound is introduced as a crosslinking agent, and crosslinking is completed by heating in the film forming process. The introduction of the novel cross-linking agent is beneficial to the construction of a two-dimensional membrane structure and can improve the mechanical properties of the anion exchange membrane, the heating cross-linking condition is beneficial to the rapid adjustment of the cross-linking degree of the ion exchange membrane and the reduction of the swelling coefficient of the ion exchange membrane during use, and the quaternary ammonium salt alkenyl compound is beneficial to the construction of an ion exchange channel and the reduction of the membrane resistance. The ion flux is improved; the anion exchange membrane has excellent spatial size stability and membrane framework stability, strong oxidation reduction resistance, strong flexibility, long service life and the like, and can be applied to the fields of flow batteries and the like. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anion exchange membranes, and in particular relates to a preparation method and application of a novel cross-linked polyarylpyridine anion exchange membrane. Background Art

[0002] As the cornerstone of energy in the new era, clean energy plays a vital role in the development of the energy world in the next stage. Among them, wind, light, geothermal and tidal energy, which have relatively high energy utilization rates, have great obstacles in the transmission and use of clean energy due to their instability and discontinuity in time and space. Energy storage batteries are highly favored as an important technology for the controllable, safe and stable output of clean energy. This technology can convert unstable and discontinuous clean energy into stable and safe physical energy and chemical energy, thereby realizing the controllable output of clean energy. Liquid flow battery technology is an emerging technology for energy storage batteries, which has the advantages of safety, stability, long life, no geographical restrictions, and deep repeated charging and discharging.

[0003] Among the various components of liquid flow batteries, anion exchange membranes (AEMs) have attracted much attention because they control the ion exchange efficiency and thus affect the overall energy efficiency of liquid flow batteries. Conventional anion exchange membranes usually use aromatic compounds as the main skeleton structure, and the quaternary ammonium salt structure obtained through reactions such as quaternization provides a relatively stable ion exchange capacity. At present, most anion exchange membranes use the method of adding a cross-linking agent to construct a two-dimensional membrane structure to improve the relevant physicochemical properties of anion exchange membranes. Shi Ning's research team used biphenyl as the main chain and added triphenylbenzene as a main chain cross-linking agent to undergo condensation polymerization with 4-acetylpyridine. This structure can be used in fuel cells and vanadium flow batteries, but the overall membrane structure is too rigid, resulting in limited mechanical properties such as tensile strength (Chem. Eng. J., 2024, 151121). Chen Nanjun's research team used terphenyl and dimethylfluorene as the rigid main chain of the anion exchange membrane, and reacted with N-methylpiperidone to undergo a polycondensation reaction. They innovatively used a double-end brominated quaternary ammonium salt type compound as a cross-linker. The anion exchange membrane has excellent ion flux and conductivity, but the cross-linking occurs during the quaternization process, which limits the excessive cross-linking degree of the ion exchange membrane, and the rotation of the piperidine ring in the main chain is restricted. The cross-linker further reduces the elongation at break of the ion membrane and limits the assembly conditions during use (J. Mater. Chem. A, 2022, 10, 3678-3687). Hu Chuan's team used terphenyl, bibenzyl and N-methylpiperidone as raw materials to prepare the main chain of the anion exchange membrane, and used 4-vinylbenzyl chloride as a side chain cross-linker. The structure has excellent mechanical properties such as tensile strength, but the properties such as elongation at break are not outstanding (J. Membr. Sci., 2021, 638, 119685). The anion exchange membranes currently used in flow batteries have the following problems: 1) Some main chains are too weak in rigidity or too strong after adding main chain crosslinkers, resulting in defects in the physical and mechanical properties of the ion exchange membrane, which brings difficulties to the mechanical assembly of the battery; 2) The two-dimensional membrane structure constructed to reduce the swelling coefficient and the transmembrane permeability of the electrolyte has a low degree of crosslinking due to the choice of crosslinking agent, and cannot effectively suppress the ultimate goal of capacity attenuation caused by transmembrane permeation of the electrolyte; 3) The ion flux brought by the hydrophobic side chain is low, which leads to an increase in the resistance of the anion exchange membrane, thereby reducing the energy efficiency of the flow battery, and its oxidation resistance brings new challenges to the ion exchange membrane. Summary of the invention

[0004] In order to solve the above problems, the present invention discloses a preparation method and application of a novel cross-linked polyarylpyridine anion exchange membrane. The novel cross-linked polyarylpyridine anion exchange membrane disclosed by the present invention uses an aromatic compound and 4-acetylpyridine polycondensation to form a main chain with both excellent rigidity and flexibility, introduces a quaternary ammonium salt type olefinic compound as a cross-linking agent, heats during the film formation process to complete cross-linking, and the cross-linked side chain has excellent microscopic phase separation characteristics. The overall ion exchange membrane has excellent redox resistance, stable low swelling degree, excellent ion flux, wide applicability, low resistance impedance, excellent mechanical properties (elongation at break> 90%), simple process and the like.

[0005] To achieve the above object, the technical solution of the present invention is as follows:

[0006] The present invention provides a novel cross-linked polyarylpyridine anion exchange membrane, wherein the novel cross-linked polyarylpyridine anion exchange membrane is prepared by forming a novel cross-linked polyarylpyridine anion exchange membrane powder into a film; the structure of the novel cross-linked polyarylpyridine anion exchange membrane powder is shown in Formula 2, and the structure of the novel cross-linked polyarylpyridine anion exchange membrane is shown in Formula 1:

[0007]

[0008] Wherein, Ar is independently any one or more of benzene, diphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, fluorene, and dimethylfluorene;

[0009] In formula 2 One or more of the following structures:

[0010]

[0011] 0≤m≤10000, 10≤n≤10000, 1≤a≤10, 1≤b≤10.

[0012] The present invention also provides a method for preparing the novel cross-linked polyarylpyridine anion exchange membrane as described above, comprising the following steps:

[0013] (1) reacting an aromatic compound and 4-acetylpyridine in dichloromethane under the catalytic action of a superacid catalyst for 24-72 hours at -10-20°C, soaking, hardening, and crushing in a 1M sodium hydroxide aqueous solution, washing with deionized water for multiple times, and drying at 105°C to obtain a polymer intermediate;

[0014]

[0015] (2) adding the polymer intermediate obtained in step (1) and a quaternary ammonium salt type alkenyl halide to an organic solvent at 35-80° C., reacting for 48-72 hours, adding iodomethane, and reacting for another 24-72 hours. After the reaction is completed, adding acetone, precipitating a solid product, washing, and drying to obtain a membrane powder;

[0016]

[0017] (3) The membrane powder obtained in step (2) is stirred evenly in an organic solvent, and the mixed homogeneous viscous solution is spread on a PET material base film, maintaining a thickness of 500-800 μm, and dried at 60-120° C. to obtain a novel cross-linked polyarylpyridine anion exchange membrane.

[0018] Furthermore, in step (1), the molar ratio of the aromatic compound to 4-acetylpyridine is 1:0.9-2.8, and the molar ratio of the aromatic compound to dichloromethane to the superacid catalyst is 1:6-10:11-21.

[0019] Furthermore, in step (1), the superacid catalyst includes one or more of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, and tellurium pentafluoride; the aromatic compound includes any one or more of benzene, diphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, fluorene, and dimethylfluorene.

[0020] Furthermore, in step (2), the molar ratio of the repeating unit of the polymer intermediate, the quaternary ammonium salt type alkenyl halide, and methyl iodide is 1:0.05-0.8:2-6.5; and the mass ratio of the polymer intermediate to the organic solvent is 1:4-10.

[0021] Furthermore, in step (2), the volume ratio of the organic solvent to acetone is 1:2-8.

[0022] Further, in step (2), the organic solvent includes one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone;

[0023] The quaternary ammonium salt type alkenyl halide comprises one of the following structures, wherein X is one of Cl, Br, and I;

[0024]

[0025] The side containing the alkenyl group is a styrene structure, under which the alkenyl group has the highest activity; or a propylene structure, which has the smallest steric hindrance and the shortest chain length, and the strong electron-withdrawing structure of the quaternary ammonium salt can make the alkenyl group thermal cross-linking have a higher reactivity.

[0026] The shortest ring-shaped and chain-shaped tertiary amine structures are used in the middle to ensure that different structures under the general short chain can be suitable for synthesizing the cross-linking agent.

[0027] The overall chain length of quaternary ammonium salt-type alkenyl halides is moderate and flexible, and after cross-linking, they can meet the expected requirements of reducing the swelling coefficient; excessively long cross-linking structures will render the constructed two-dimensional membrane structure ineffective due to excessive flexibility.

[0028] Furthermore, in step (3), the mass ratio of the membrane powder to the organic solvent is 1:4-14; the organic solvent comprises one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0029] The present invention also provides an application of the novel cross-linked polyarylpyridine anion exchange membrane in a liquid flow battery.

[0030] The present invention also provides an application of a novel cross-linked polyarylpyridine anion exchange membrane prepared by the preparation method described above in a liquid flow battery.

[0031] The beneficial effects of the present invention are:

[0032] (1) The dense ether-free polymer main chain reduces the water absorption of the main skeleton chain, thus ensuring the spatial stability of the skeleton and the ion flux of small ions.

[0033] (2) The introduction of side chain cross-linking agents constructs a planar two-dimensional rigid membrane structure, enhances the redox resistance of the anion exchange membrane, reduces the swelling coefficient, and inhibits the battery capacity decay during use.

[0034] (3) The introduction of a high-polymerization aromatic skeleton and a flexible side chain cross-linking agent increases the flexibility of the side chain while ensuring the rigidity of the polymerized monomer, thereby improving the overall mechanical properties of the anion exchange membrane, such as tensile strength and elongation at break.

[0035] (4) The flexible pyridine part and the highly flexible quaternary amine side chain in the polyaryl pyridine main chain increase the collision probability in the cross-linking reaction and enhance the reactivity of the cross-linking reaction.

[0036] (5) The side chain introduces a quaternary ammonium salt type olefinic compound as a crosslinking agent, so that the R4N + The relative content is improved, which can effectively construct a microscopic phase separation structure, which is beneficial to construct a stable ion transmission channel to increase the ion flux.

[0037] (6) quaternary ammonium salt type olefinic compound is used as a cross-linking agent, and cross-linking occurs under heating conditions, thereby avoiding the occurrence of cross-linking during the quaternization reaction, reducing the difficulty of the quaternization reaction, and increasing the possibility of a highly cross-linked anion exchange membrane. At the same time, the quaternary ammonium salt type olefinic compound has a higher reactivity due to the strong electron-withdrawing structure of the quaternary ammonium salt. The quaternary ammonium salt type olefinic cross-linking agent used in the present invention can provide the following effects at the same time, including a simpler and faster cross-linking reaction, a larger cross-linking degree, a more stable two-dimensional membrane construction, an improvement in mechanical properties brought about by the flexible side chain, and an improvement in ion flux brought about by the quaternary ammonium salt structure.

[0038] The novel cross-linked polyarylpyridine anion exchange membrane prepared by the present invention has the advantages of high ion flux, strong exchange capacity, high mechanical properties, low membrane resistance, etc., while ensuring the advantages of excellent membrane skeleton stability, strong anti-swelling property, excellent corrosion resistance and long service life, and can be used in fields such as liquid flow batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The hydrogen nuclear magnetic resonance spectrum of the polymer intermediate prepared in step (1) of Example 1 of the present invention in deuterated chloroform;

[0040] Figure 2 The hydrogen nuclear magnetic resonance spectrum of the quaternary ammonium salt type alkenyl halide in deuterated water used in step (2) of Example 1 of the present invention;

[0041] Figure 3 The nuclear magnetic resonance hydrogen spectrum of the membrane powder prepared in step (2) of Example 1 of the present invention in deuterated dimethyl sulfoxide;

[0042] Figure 4 This is a schematic diagram of the scraping film preparation of the novel cross-linked polyarylpyridine anion exchange membrane prepared in step (3) of Example 1 of the present invention;

[0043] Figure 5 This is a schematic diagram of the swelling of the novel cross-linked polyarylpyridine anion exchange membrane prepared in step (3) of Example 1 of the present invention while immersed in dimethyl sulfoxide;

[0044] Figure 6 The GPC data of the membrane powder prepared in step (2) and the anion exchange membrane prepared in step (3) of Example 1 of the present invention are shown;

[0045] Figure 7 The nuclear magnetic resonance hydrogen spectrum of the membrane powder prepared in step (1) of comparative example 1 of the present invention in deuterated dimethyl sulfoxide;

[0046] Figure 8 The nuclear magnetic resonance hydrogen spectrum of the membrane powder prepared in step (1) of comparative example 2 of the present invention in deuterated dimethyl sulfoxide;

[0047] Fig. 9 The nuclear magnetic resonance hydrogen spectrum of the membrane powder prepared in step (2) of comparative example 3 of the present invention in deuterated dimethyl sulfoxide;

[0048] Fig.10 The cycle number diagram of the coulombic efficiency, energy efficiency and voltage efficiency of the novel cross-linked polyarylpyridine anion exchange membrane prepared in step (3) of Example 1 of the present invention in the charge and discharge cycle test in an organic liquid flow battery;

[0049] Fig.11 This is a graph showing the cycle number of the charge and discharge capacity of the novel cross-linked polyarylpyridine anion exchange membrane prepared in step (3) of Example 1 of the present invention in a charge and discharge cycle test in an organic liquid flow battery. DETAILED DESCRIPTION

[0050] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0051] Example 1

[0052]

[0053] Step (1) Synthesis of polymer intermediate

[0054] Place p-terphenyl (25.0 g, 0.109 mol), m-terphenyl (25.0 g, 0.109 mol), 4-acetylpyridine (45.77 g, 0.37 mol) and dichloromethane (100 mL) into a 1000 mL reactor, cool to -5±5°C, slowly drop trifluoromethanesulfonic acid (405.0 g, 2.74 mol); after the addition is completed, keep the temperature at -5°C, stir and react for 50 hours, pour the dark blue viscous liquid obtained by the reaction into a 1M sodium hydroxide aqueous solution, stir sufficiently, wash the obtained white precipitate with water until it is neutral, and dry to obtain 70.06 g of a polymer intermediate with a yield of 96.38%. The hydrogen nuclear magnetic resonance spectrum of the polymer intermediate obtained in step (1) in deuterated chloroform is as follows: Figure 1 shown.

[0055] Step (2) Preparation of membrane powder:

[0056] The polymer intermediate (40.0 g) obtained in step (1), dimethyl sulfoxide (200.0 g) and quaternary ammonium salt type alkenyl halide (as shown in Formula 3) (4.7 g) were added to a 500 mL round-bottom flask and stirred at 75° C. for 48 h; then iodomethane (51.0 g) was added to the round-bottom flask, the temperature was maintained at 75° C., and the reaction was stirred for 36 h to obtain a dark brown viscous liquid, which was added to acetone (500 mL) and stirred thoroughly. The obtained yellow precipitate was washed with deionized water for several times, dried and crushed to obtain 56.2 g of light yellow film powder, the structure of which is shown in Formula 2. The nuclear magnetic resonance hydrogen spectrum of the quaternary ammonium salt type alkenyl halide of Formula 3 used in step (2) in deuterated water is as follows: Figure 2 As shown, the H NMR spectrum of the prepared membrane powder in deuterated dimethyl sulfoxide is as follows Figure 3 shown.

[0057]

[0058] Step (3) Preparation of anion exchange membrane:

[0059] The membrane powder (20.0 g) obtained in step (2) and dimethyl sulfoxide (240.0 g) were added to a 500 mL round-bottom flask and stirred thoroughly to form a uniform solution. The solution was poured onto a PET base film, scraped flat, heated to 90-105° C. and allowed to stand for 4 h to obtain an anion exchange membrane with a thickness of 58±4 μm. The membrane preparation stage was as follows: Figure 4 shown.

[0060] The novel cross-linked polyarylpyridine anion exchange membrane prepared in step (3) is tested for its ion exchange capacity, water absorption, ion conductivity, scattering vector and elongation at break according to the national standard GB / T 1040-92 method, and the data are shown in Table 1 below. The novel cross-linked polyarylpyridine anion exchange membrane disclosed in the present invention has excellent tensile strength due to its rigid terphenyl main chain. The flexible quaternary ammonium salt type alkenyl compound used in the quaternization reaction as a side chain with a moderate chain length enhances the toughness of the overall membrane, so that the anion exchange membrane has excellent elongation at break. The R4N brought by the quaternary ammonium salt type alkenyl compound on the side chain + The increase in the relative content of the structure has excellent ion exchange conductivity.

[0061] Table 1

[0062]

[0063] After the prepared novel cross-linked polyarylpyridine anion exchange membrane was tested for relevant properties, it was immersed in dimethyl sulfoxide again. The anion exchange membrane could not be completely dissolved and swelling occurred. Figure 5As shown, it is shown that the quaternary ammonium salt type olefinic compound as a cross-linking agent undergoes a cross-linking reaction during the scraping process, and the cross-linked anion exchange membrane cannot be completely dissolved. The GPC data of the membrane powder prepared in step (2) and the anion exchange membrane prepared in step (3) are shown in FIG. Figure 6 As shown, the red line is the anion exchange membrane data, and the blue line is the membrane powder data. The molecular weight of the anion exchange membrane in the figure is much larger than the molecular weight of the membrane powder, proving that a cross-linking reaction occurred during the scraping process, resulting in an increase in the molecular weight.

[0064] Comparative Example 1

[0065]

[0066] Step (1) Preparation of membrane powder

[0067] The polymer intermediate (40.0 g) obtained in step (1) of Example 1, dimethyl sulfoxide (200.0 g) and 5-bromo-1-pentene (2.7 g) were placed in a 500 mL round-bottom flask and stirred at 85° C. for 48 h. Then, methyl iodide (51.0 g) was added to the round-bottom flask, and the mixture was kept at 35° C. and stirred for 24 h to obtain a reddish brown viscous liquid, which was added to acetone (500 mL) and stirred thoroughly. The obtained yellow precipitate was washed with deionized water several times, dried and crushed to obtain 53.2 g of light yellow membrane powder, the structure of which is shown in Formula 4. The hydrogen nuclear magnetic resonance spectrum of the prepared membrane powder in deuterated dimethyl sulfoxide is as follows: Figure 7 shown.

[0068] Step (2) Preparation of anion exchange membrane:

[0069] The membrane powder (20.0 g) obtained in step (1) of comparative example 1 and dimethyl sulfoxide (160.0 g) were added to a 500 mL round-bottom flask and stirred thoroughly to form a uniform solution. The solution was poured onto a PET base film, scraped flat, and heated to 90-105° C. and allowed to stand for 4 h to obtain an anion exchange membrane with a thickness of 58±4 μm.

[0070] The anion exchange membrane obtained in step (2) of comparative example 1 was immersed in dimethyl sulfoxide again, and it was found that the anion exchange membrane was completely dissolved, which was different from that in example 1. Figure 5 The swelling is completely different, indicating that the anion exchange membrane prepared in Comparative Example 1 cannot be cross-linked to form a two-dimensional membrane even if there is an olefinic structure that can undergo a cross-linking reaction. It is proved that the olefinic cross-linking agent with a quaternary ammonium salt structure has a faster cross-linking rate and a more stable structure under heating conditions.

[0071] Comparative Example 2

[0072]

[0073] Step (1) Preparation of membrane powder

[0074] The polymer intermediate (40.0 g) obtained in step (1) of Example 1, dimethyl sulfoxide (200.0 g) and 4-vinylbenzyl chloride (2.9 g) were placed in a 500 mL round-bottom flask and stirred at 45° C. for 48 h. Then, methyl iodide (51.0 g) was added to the round-bottom flask, and the mixture was kept at 35° C. and stirred for 24 h to obtain a brown viscous liquid, which was added to acetone (500 mL) and stirred thoroughly. The obtained yellow precipitate was washed with deionized water several times, dried and crushed to obtain 54.6 g of light yellow membrane powder, the structure of which is shown in Formula 5. The hydrogen nuclear magnetic resonance spectrum of the prepared membrane powder in deuterated dimethyl sulfoxide is as follows: Figure 8 shown.

[0075] Step (2) Preparation of anion exchange membrane:

[0076] The membrane powder (20.0 g) obtained in step (1) of comparative example 2 and dimethyl sulfoxide (165.0 g) were added to a 500 mL round-bottom flask and stirred thoroughly to form a uniform solution. The solution was poured onto a PET base film, scraped flat, and heated to 90-105° C. and allowed to stand for 4 h to obtain an anion exchange membrane with a thickness of 58±4 μm.

[0077] The anion exchange membrane obtained in step (2) of Comparative Example 2 was immersed in dimethyl sulfoxide again, and it was found that the anion exchange membrane was not completely dissolved, which was different from that in Example 1. Figure 5 The swelling is similar to that shown. The tensile strength and elongation at break were tested according to the national standard GB / T 1040-92 method, and the relevant data of the anion exchange membrane obtained in Example 1 and Comparative Example 1 were compared, as shown in Table 2. It shows that the anion exchange membrane with 4-vinylbenzyl chloride as the crosslinking agent is also crosslinked because of its poor side chain flexibility after crosslinking. Although it is similar to the anion exchange membrane that has completed crosslinking in Example 1, it has an increase in tensile strength compared with the uncrosslinked anion exchange membrane in Comparative Example 1, but a significant decrease in elongation at break, proving that only flexible side chain crosslinking can simultaneously improve tensile strength and elongation at break.

[0078] Table 2

[0079] Membrane Type Elongation at break / % Tensile strength / Mpa Remark Example 1 103.1 48.4 Flexible cross-linking Comparative Example 1 80.6 38.6 Not cross-linked Comparative Example 2 56.8 51.1 Rigid cross-linking

[0080] Comparative Example 3

[0081]

[0082] Step (1) Synthesis of polymer intermediate

[0083] Into a 1000mL reactor, p-terphenyl (25.0g, 0.109mol), m-terphenyl (25.0g, 0.109mol), N-methylpiperidone (30.0g, 0.27mol) and dichloromethane (100mL) were added, the temperature was lowered to -5±5℃, trifluoroacetic acid (35.0g, 0.307mol) and trifluoromethanesulfonic acid (370.0g, 2.47mol) were slowly added dropwise; after the addition was completed, the temperature was maintained at -5℃, the reaction was stirred for 24h, the dark purple viscous liquid obtained by the reaction was poured into a 1M sodium hydroxide aqueous solution, after sufficient stirring, the obtained white precipitate was washed with water until neutral, and dried to obtain 67.06g of a polymer intermediate with a yield of 94.81%.

[0084] Step (2) Preparation of membrane powder:

[0085] The polymer intermediate (39.0 g) obtained in step (1) of comparative example 3, dimethyl sulfoxide (260.0 g) and quaternary ammonium salt type alkenyl halide (as shown in formula 3) (4.7 g) were added to a 500 mL round-bottom flask and stirred at 75° C. for 48 h; then iodomethane (51.0 g) was added to the round-bottom flask, and the temperature was maintained at 75° C. and stirred for 36 h to obtain a dark brown viscous liquid, which was added to acetone (800 mL) and stirred thoroughly. The obtained yellow precipitate was washed with deionized water several times, dried and crushed to obtain 54.8 g of light yellow membrane powder, the structure of which is shown in formula 6. The nuclear magnetic resonance hydrogen spectrum of the prepared membrane powder in deuterated dimethyl sulfoxide is as follows: Fig. 9 shown.

[0086] Step (3) Preparation of anion exchange membrane:

[0087] The membrane powder (40.0 g) obtained in step (2) of comparative example 3 and dimethyl sulfoxide (140.0 g) were added to a 500 mL round-bottom flask, and the mixture was stirred thoroughly to form a uniform solution. The solution was poured onto a PET base film, scraped flat, and heated to 90-105° C. and allowed to stand for 4 h to obtain an anion exchange membrane with a thickness of 56±4 μm.

[0088] The tensile strength and elongation at break of the anion exchange membrane obtained in step (3) of comparative example 3 were tested according to the national standard GB / T 1040-92 method, and the relevant data of the anion exchange membrane obtained in Example 1 were compared, as shown in Table 3 below. Although an anion exchange membrane can be obtained by using a flexible quaternary ammonium salt-type olefin cross-linking agent under the condition of a rigid structural main chain, the physical and mechanical properties of the membrane, especially the elongation at break, are greatly reduced, which limits the assembly conditions during the subsequent use of the battery.

[0089] Table 3

[0090] Membrane Type Elongation at break / % Tensile strength / Mpa Remark Example 1 103.1 48.4 With flexible structural main chain Comparative Example 3 34.6 42.9 Rigid structural main chain

[0091] Example 2

[0092] Organic liquid flow battery application: The novel cross-linked polyarylpyridine anion exchange membrane prepared in step (3) of the above embodiment 1 is assembled in the battery cell, the positive and negative electrolytes are respectively of formula 7 and formula 8, the supporting electrolyte is sodium chloride, and the constant power is 128 mW / cm in a 25°C constant temperature box. 2 Carry out cyclic charge and discharge test, such as Fig.10 As shown, the coulomb efficiency is 99.79% (constant current and constant voltage) 99.81% (constant power), the voltage efficiency is 84.61% (constant current and constant voltage) 85.54% (constant power), and the energy efficiency is 84.43% (constant current and constant voltage) 85.34% (constant power). The charge and discharge capacity of the battery test is shown in Fig.11 As shown, the capacity decay under constant power is as low as 0.010% / turn.

[0093]

[0094] It should be noted that the above content only illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A novel cross-linked polyarylpyridine anion exchange membrane, characterized in that: The novel cross-linked polyarylpyridine anion exchange membrane is prepared by forming a new cross-linked polyarylpyridine anion exchange membrane powder into a membrane; The structure of the novel cross-linked polyarylpyridine anion exchange membrane powder is shown in Formula 2, and the structure of the novel cross-linked polyarylpyridine anion exchange membrane is shown in Formula 1; Wherein, Ar is independently any one or more of benzene, diphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, fluorene, and dimethylfluorene; In formula 2 One of the following structures: 0≤m≤10000, 10≤n≤10000, 1≤a≤10, 1≤b≤10.

2. A method for preparing a novel cross-linked polyarylpyridine anion exchange membrane, characterized in that: The following steps are involved: (1) reacting an aromatic compound and 4-acetylpyridine in dichloromethane under the catalytic action of a superacid catalyst for 24-72 hours at -10-20°C, soaking, hardening, and crushing in a 1M sodium hydroxide aqueous solution, washing with deionized water for multiple times, and drying at 105°C to obtain a polymer intermediate; (2) adding the polymer intermediate obtained in step (1) and a quaternary ammonium salt type alkenyl halide to an organic solvent at 35-80° C., reacting for 48-72 hours, adding iodomethane, and reacting for another 24-72 hours. After the reaction is completed, adding acetone, precipitating a solid product, washing, and drying to obtain a membrane powder; (3) stirring the membrane powder obtained in step (2) in an organic solvent, spreading the mixed and homogeneous viscous solution on a PET base film, maintaining a thickness of 500-800 μm, and drying at 60-120° C. to obtain a novel cross-linked polyarylpyridine anion exchange membrane; Wherein, Ar is independently any one or more of benzene, diphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, fluorene, and dimethylfluorene; The quaternary ammonium salt type alkenyl halide comprises one or more of the following structures; 0≤m≤10000, 10≤n≤10000, 1≤a≤10, 1≤b≤10, X is one of Cl, Br, and I.

3. The method for preparing a novel cross-linked polyarylpyridine anion exchange membrane according to claim 2, characterized in that: In step (1), the molar ratio of the aromatic compound to 4-acetylpyridine is 1:0.9-2.8, and the molar ratio of the aromatic compound to dichloromethane to the superacid catalyst is 1:6-10:11-21.

4. The method for preparing a novel cross-linked polyarylpyridine anion exchange membrane according to claim 3, characterized in that: The superacid catalyst includes one or more of trifluoroacetic acid, methanesulfonic acid, trifluoromethanesulfonic acid, and tellurium pentafluoride; the aromatic compound includes any one or more of benzene, diphenyl, p-terphenyl, m-terphenyl, p-quaterphenyl, fluorene, and dimethylfluorene.

5. The method for preparing a novel cross-linked polyarylpyridine anion exchange membrane according to claim 2, characterized in that: In step (2), the molar ratio of the repeating unit of the polymer intermediate, the quaternary ammonium salt type alkenyl halide, and methyl iodide is 1:0.05-0.8:2-6.5; and the mass ratio of the polymer intermediate to the organic solvent is 1:4-10.

6. The method for preparing a novel cross-linked polyarylpyridine anion exchange membrane according to claim 2, characterized in that: In step (2), the organic solvent is one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

7. The method for preparing a novel cross-linked polyarylpyridine anion exchange membrane according to claim 2, characterized in that: In step (3), the mass ratio of the membrane powder to the organic solvent is 1:4-14.

8. The method for preparing a novel cross-linked polyarylpyridine anion exchange membrane according to claim 2, characterized in that: In step (3), the organic solvent includes one or more of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, and N-methylpyrrolidone.

9. Use of the novel cross-linked polyarylpyridine anion exchange membrane as claimed in claim 1 in a liquid flow battery.

10. Use of a novel cross-linked polyarylpyridine anion exchange membrane prepared by the preparation method according to any one of claims 2 to 8 in a liquid flow battery.

Citation Information

Cited By

  • Auxiliary cross-linking type polyarylpyridine anion exchange membrane as well as preparation method and application thereof

    CN120637548A

  • Auxiliary crosslinking type polyarylpyridine anion exchange membrane, its preparation method and application

    CN120637548B